Effect of Addition of Different Levels of Soya Flour and Rice Flour as Extenders on Quality of Quail Meatballs and Economics - Dhond, U.V.; Devangare, A. A.; Chappalwar, A. M. (Journal of Meat Science, 2016)
The study was undertaken with an aim to develop acceptable quality meatballs from quail meat incorporated with different extenders. Minced quail meat, spices, condiments and extenders (soya and rice flour) were used for preparation of quail meatballs. The extenders were found useful in improving physico-chemical characteristics of quail meatballs. The scores for all sensory attributes viz. appearance, flavour, juiciness, texture and overall palatability decreased gradually with increase in the level of incorporation of soya flour and rice flour up to 2.5% level. Increase in addition of soya flour and rice flour levels in formulation showed significant (p<0.05) decrease in all sensory attributes. Among the treatment, the product prepared from quail meat incorporated with 2.5 percent soya exhibited significantly higher score for all sensory attributes and physico-chemical characteristic. Quail meatballs prepared by using rice flour showed gradual decrease in sensory attributes and physico-chemical characteristic. It is also revealed that the cost of production of control meatballs was Rs. 3.39 which was higher than that of soya and rice flour extended meatballs.